Vegetation survey and accuracy assessment of vegetation mapping at Fort Union National Monument, New Mexico - Muldavin, Esteban, author; Chauvin, Yvonne, author; Browder, Amanda, author; Neville, Terry, author; United States. National Park Service, publisher (Colorado State University. Libraries, 2012)
The Fort Union National Monument (FOUN) is located on the western high plains of north central New Mexico and was an important military and civilian site in the development of the southwestern United States. A classification and map of the vegetation at FOUN were created in 2004 by ecologists with Natural Heritage New Mexico (NHNM) and published as Muldavin et al. (2004). An accuracy assessment (AA) of the FOUN vegetation map was conducted in 2009 by ecologists with the Colorado Natural Heritage Program (CNHP) and published internally as Stevens and Sever (2011). This document was compiled from those efforts by Joe Stevens and Travis Talbot, ecologists with CNHP, and includes both the vegetation inventory and the AA information reformatted to have a consistent flow and eliminate overlaps and duplications.
Keywords: ecology; vegetation mapping and classification